Environmental emissions at foundation construction stage of buildings – Two case studies. (January 2016) - Sandanayake, Malindu; Zhang, Guomin; Setunge, Sujeeva
Abstract: Foundation construction involves heavy machine usage which contributes to greenhouse gas (GHG) and non-GHG emissions. The study aims to develop a model to estimate and compare emissions at foundation construction and demonstrate its application using two case studies. A process-based quantitative method is established to estimate emissions due to materials, transportation, and equipment usage. The results are analysed under five impact categories including Global Warming Potential, Acidification Potential, Eutrophication Potential, Photochemical Oxidant Formation Potential and Human Toxicity Potential. Analytical Hierarchy Process is employed to obtain weighting factors to assess impact categories under global and local perspectives. Results obtained an average GHG emission of 67%, 19% and 14% from materials, equipment and transportation respectively. This observation signifies the relative higher percentage of emission distribution of equipment and transportation in foundation construction compared to that in the total building construction. Considerable amount of non-GHG emissions such as Nitrous Oxides and Carbon Monoxides were recorded. Global Warming Potential remained the most prominent impact potential from all the perspectives considered, with an overpowering 75% contribution from global perspective. However, this relative importance is reduced to 33.74%–34.85%, with a relative increase in Photochemical Oxidant Formation and Eutrophication Potentials to 32.55% and 31.92% at regional and local perspective. Therefore emissions such as Nitrogen Oxides, Carbon Monoxides and Sulphur Dioxide should be given more consideration at the regional and local perspectives. Results also convey that the emission comparison perspective could change the focus of environmental impacts considerably. Highlights: GHG emissions due to equipment usage are significant in foundation construction. Considerable amount of non-GHG emissions is recorded in foundation construction. Global Warming Potential is the most prominent impact category. Photochemical Oxidant Formation Potential is significant at regional perspective. Eutrophication potential is significant at local perspective.